2017
DOI: 10.1101/225714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systems genetics identifies modifiers of Alzheimer’s disease risk and resilience

Abstract: SummaryIdentifying genes that modify symptoms of Alzheimer's disease (AD) will provide novel therapeutic strategies to prevent, cure or delay AD. To discover genetic modifiers of AD, we combined a mouse model of AD with a genetically diverse reference panel to generate F1 mice harboring identical 'high-risk' human AD mutations but which differ across the remainder of their genome. We first show that genetic variation profoundly modifies the impact of causal human AD mutations and validate this panel as an AD m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…When including genotype and BXD background strain, PLD3 remained predictive of learning acquisition speed (β = 0.04, p = 0.003) but not when modeling fear memory recall (β = 0.085, p = 0.08). These findings are unsurprising as the main effect for the AD-BXD behavioral stratification was observed upon learning acquisition slope rather than memory recall, as recall is more strongly sensitive to β-amyloid burden [ 14 , 15 ]. Collectively, these human and animal data suggest that PLD3 expression is linked to cognition in the aged brain.…”
Section: Resultsmentioning
confidence: 99%
“…When including genotype and BXD background strain, PLD3 remained predictive of learning acquisition speed (β = 0.04, p = 0.003) but not when modeling fear memory recall (β = 0.085, p = 0.08). These findings are unsurprising as the main effect for the AD-BXD behavioral stratification was observed upon learning acquisition slope rather than memory recall, as recall is more strongly sensitive to β-amyloid burden [ 14 , 15 ]. Collectively, these human and animal data suggest that PLD3 expression is linked to cognition in the aged brain.…”
Section: Resultsmentioning
confidence: 99%
“…In 5xFAD mice, females also show more AD‐related pathology than males, including increased Aβ‐plaque load, and elevated levels of APP and Aβ‐42 as early as 4‐6 months of age (Sadleir et al, 2015) . These sex differences cannot simply be attributed to differences in transgene expression, given similar levels of hAPP and hPS1 mRNA have been observed in male and female 5xFAD mice …”
Section: Discussionmentioning
confidence: 99%
“…31 These sex differences cannot simply be attributed to differences in transgene expression, given similar levels of hAPP and hPS1 mRNA have been observed in male and female 5xFAD mice. 49 Previous studies documenting motor dysfunction in 5xFAD mice have used only one sex of 5xFAD mice, 22,24 and this is the first study to examine sex differences in motor impairments. Consistent with previous studies, we reliably detected motor impairment in both male and female 5xFAD mice, and found that age-related progression of motor impairment was generally consistent across sexes.…”
Section: Are There Sex Differences In the Progression Of The Motor mentioning
confidence: 99%
“…When including genotype (β-amyloid state) and BXD background strain, PLD3 remained predictive of learning acquisition speed (β=0.04, p=0.003) but not when modeling fear memory recall (β=0.085, p=0.08). These findings are unsurprising as the main effect for the AD-BXD behavioral stratification was observed upon learning acquisition slope rather than memory recall, as memory recall is more strongly sensitive to β-amyloid burden 17,20 . Collectively, these human and animal data suggest that PLD3 expression has a direct impact upon cognition in the aged brain.…”
Section: Pld3 Mrna Levels Are Lower In Ad-bxd Mice and Correlated Witmentioning
confidence: 99%